UPACARA PENGANTIN MAKAN NASI HADAP- HADAPAN SEBAGAI SYMBOL CINTA DAN RAHMAH DALAM ADAT MELAYU: ANALISIS TAFSIR AYAT- AYAT AL- QUR’AN TERHADAP KONSEP KASIH SAYANG - Viska Aprilia Kusuma; Suci Cahyani; Dea Ananda Wilianca (Al Arsy: Journal of Education, Management and Islamic Thought, 2025)
Marriage in Islam is a sacred institution aimed at forming a harmonious family grounded in the values of sakinah, mawaddah, and rahmah. In social practice, the implementation of marriage often interacts with customary traditions that develop within society as expressions of culture and local identity. One tradition that continues to be preserved in Malay customary weddings is the face-to-face rice-eating tradition, which carries symbolic meaning in shaping the relationship between husband and wife as well as strengthening ties between families. This article aims to analyze the symbolic meaning of the face-to-face rice-eating tradition and examine its relevance to the concept of compassion from a Qur’anic perspective. The study employs a qualitative method with a library research approach, using descriptive-analytical analysis of Qur’anic exegetical sources, particularly interpretations of QS. Ar-Rum: 21, QS. Maryam: 96, QS. Al-Mumtahanah: 7, QS. Al-Isra’: 24, and QS. Al-Balad: 17, as well as scholarly literature discussing Malay wedding customs. The findings indicate that the face-to-face rice-eating tradition embodies values of togetherness, cooperation, responsibility, empathy, and compassion that are consistent with the Islamic principles of mawaddah and rahmah. This tradition represents a form of local cultural effort to internalize Qur’anic values within family life. As long as it does not contradict Islamic creed and law, the tradition can be understood as a cultural expression that strengthens the formation of a sakinah family. Thus, custom and religion are not positioned in mutual negation, but rather complement and reinforce one another in fostering harmony within Muslim families.